Agriculture is special: conclusions drawn from the death throes of the Doha round for a development-friendly agricultural trade policy - Michael Brüntrup; Clara Brandi; Nikolai Fuchs (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The Doha Round of World Trade Organization (WTO)talks is in its death throes. It could provide urgently needed stimuli for a rule-based enhancement of international trade, but there is currently no consensus on some of the main sticking-points. Probably the most important of these is the liberalisation of the agricultural sector. Whatever follows Doha, no significant progress will be made in the multilateral negotiations unless adequate account is taken of the circumstances and needs of both the developing and the industrialised countries in agricultural trade issues. The agricultural sector has many peculiarities, but where liberalisation is concerned, the conclusions for rich and poor countries differ. The following six conclusions can be drawn from the Doha Round talks: The discussions on the agricultural sector should continue within the WTO framework. In only very few instances do the bilateral trade agreements that are becoming increasingly numerous as the Doha Round goes into decline offer developing countries with an agricultural focus as strong a bargaining position as they have in the WTO framework; in particular, they are incapable of curbing subsidies in the industrialised countries. Exempting developing countries from the general liberalisation of the agricultural sector is justified. This sector is often crucial to poverty reduction and food security, being the most important source of income for small farmers, who account for by far the largest proportion of the poor and hungry. Agrobased industrialisation and food economy also form the core component of the development of many poor countries, which is often impossible unless they receive special support and protection, especially at a time of distorted world markets. On the other hand, developing countries must realise that protection of and support for their agricultural sectors should be regulated in a transparent and contestable way – if only to promote South-South trade and the stability of world food markets. In industrialised countries the food supply level is so high that they do not need to ensure food security by promoting the availability of food or pursuing price policies such that production and trade are distorted. There are enough alternative approaches to dealing with such problems as rising world market prices, foremost among them being the strengthening of social protection systems. Special consideration of the multifunctionality of agriculture in agricultural and environmental policies is legitimate, but should be achieved with instruments (such as requiring or specifically promoting the preservation of cultural landscapes, biodiversity or water conservation) that do not, as far as possible, generate any hidden production or trade distortions, unlike both conventional price subsidies and the currently widespread direct area payments, for example. Food export restrictions should be limited to protecting importing countries and smoothing out price fluctuations.
Keywords: 330